Distributions of vesicular glutamate transporters 1 and 2 in the visual thalamus and associated areas of the cat. Issue 7 (11th November 2021) - Abbas Farishta, Reza; Zouahi, Hadjer; Casanova, Christian
Abstract: Glutamate is packaged in vesicles via two main vesicular transporter (VGLUT) proteins, VGLUT1 and VGLUT2, which regulate its storage and release from synapses of excitatory neurons. Studies in rodents, primates, ferrets, and tree shrews suggest that these transporters may identify distinct subsets of excitatory projections in visual structures, particularly in thalamocortical pathways where they tend to correlate with modulatory and driver projections, respectively. Despite being a well‐studied model of thalamocortical connectivity, little is known about their expression pattern in the cat visual system. To expand current knowledge on their distribution and how they correlated with known driver and modulator projecting sites, we examined the protein expression patterns of VGLUT1 and VGLUT2 in the visual thalamus of the cat (lateral geniculate nucleus and the pulvinar complex). We also studied their expression pattern in relevant visual structures projecting to or receiving significant thalamic projections, such as the primary visual cortex and the superior colliculus. Our results indicate that both VGLUTs are consistently present throughout the cat visual system and show laminar or nuclei specificity in their distribution, which suggests, as in other species, that VGLUT1 and VGLUT2 represent distinct populations of glutamatergic projections.